Relationship Quality Of Health Services With Patient Satisfaction At Lancirang Health Center (Preventif : Jurnal Kesehatan Masyarakat, 2025)
ABSTRACTPatient satisfaction is an important indicator in assessing the success of health services, which is not always in line with the quality of services provided. In Lancirang Health Center itself, although the quality of service is relatively good, patient satisfaction in 2023 only reached 63.3%, still below the national target of 95%. This study aims to determine the relationship between the quality of health services consisting of five dimensions (reliability, assurance, tangible evidence, empathy, and responsiveness) with patient satisfaction. This study uses the quantitative method with a cross-sectional design. The random sampling technique was used with a total of 218 respondents. Data were collected through observation, questionnaires, interviews, and documentation, then analyzed using the chi-square test.  The results showed that each dimension of service quality had a significant relationship with patient satisfaction, with a p value